2022
DOI: 10.2147/rmhp.s374420
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Social Video Platforms in Promoting COVID-19 Vaccination Among Youth: A Content-Specific Analysis of COVID-19 Vaccination Topic Videos on Bilibili

et al.

Abstract: Background With the widespread promotion of the COVID-19 vaccination in China, videos about the vaccination have become increasingly available on social video platforms. With the User Generated Content model, different creators’ interpretations of COVID-19 vaccines may influence the attitudes towards the vaccines and vaccination. Objective To explore the overview of COVID-19 vaccine-related videos on Bilibili, discussing the communication effects of COVID-19 topic video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
0
6
0
2
Order By: Relevance
“…Kong et al 24 assessed the quality of the information in diabetes‐related videos on TikTok. Additionally, Gao et al 25 explored the overview of COVID‐19 vaccine‐related videos on Bilibili. Previously, an analysis was conducted to evaluate the content and quality of videos on YouTube, and the results were moderate according to common scoring systems 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al 24 assessed the quality of the information in diabetes‐related videos on TikTok. Additionally, Gao et al 25 explored the overview of COVID‐19 vaccine‐related videos on Bilibili. Previously, an analysis was conducted to evaluate the content and quality of videos on YouTube, and the results were moderate according to common scoring systems 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Following the approach proposed by Chen et al 19 , the communication effects of the videos were categorized into four dimensions: overall communication effect, communication breadth, communication recognition, and communication participation. The overall communication effect was measured using the logarithmic sum of seven indicators: shares, views, likes, favorites, coins, danmaku (bullet comment), and video comments 11 . The number of shares 19 measured communication breadth.…”
Section: Methodsmentioning
confidence: 99%
“…Bilibili, as one of the video platforms, has the youngest user base among Chinese internet users, with 90% being users aged <25 years and often associated with youth culture 9 , 10 . Previous studies have shown that Bilibili also plays a positive role in promoting health among young people 11 . Therefore, it is worth exploring whether Bilibili actively promotes smoking cessation.…”
Section: Introductionmentioning
confidence: 98%
“…The COVID-19 videos have played a major role in containing the epidemic and reducing anxiety by disseminating informative content related to the COVID-19 outbreak [4]. Therefore, COVID-19 videos are often used in the prevention and control of epidemics [5]. This epidemic has lasted for three years, and the prevention and control of the epidemic is also a constant battle.…”
Section: Introductionmentioning
confidence: 99%